Professional development through experiential learning in research: contributions of collaborative action research - Silva, Fabrício Oliveira da (2022)
This paper analyzes the contribution of collaborative action research to the professional development of student researchers. It adopts as a centrality the notion that dialogicity, reflection and the development ofrhizome research have a close relationship with the researcher’s development, by allowing him to insert himself in the research universe from a matrix project developed by a group of researchers. collaborators who reveal a certain experience in dealing with scientific research. The article aims to analyze thecontributions of the production of studies carried out based on collaborative action research for the professional development of student researchers. The methodology is of qualitative basis and was developed from the reports of scientific initiation and master’s dissertations. The study showed that the involvement of employees in collaborative action research favors the development of experiential learning by becoming a research teacher. It also reveals that rhizome research promotes reflections on the network, enabling autonomy and professional development.